A survey on the factors affecting the writing ability of pupils in English: a case study of primary six pupils of SK. St. Stephen, Bau / Nyolet Abun - Abun, Nyolet (2008)
The ability to write well is not a naturally acquired skill. It is learned in formal instructional settings or other environments. Writing skills must be practiced and learned through experience. In second language writing class, learners are confronted by planned intervention through skills specified in the curriculum. Learners may feel comfortable writing in their first language but writing in the second language is not always favoured by learners. The system of the learners’ first language, the medium they have grown up with always interfere in their writing ability. Kaplan, (1996) stated that the learners’ native culture or predisposition of one’s native language and the way they think do influence their competency when writing in the second language. Social and cognitive factors of a learner also affect the rate of second language learning which ultimately affect the writing ability. This Case Study investigates the factors that affect the writing ability of Year Six pupils in English. This study was carried out in a school where 95 percent of the class population who come from the same speech community and they share common problems pertaining to composition writing. The result showed that the factors that affect the pupils’ ability to write in English were the interference of their first language that was brought into writing in English. There was also clear relationship between cognitive ability and language performance in English among the respondents.